Gestão pública em saúde mental: um estudo em CAPS com gerência pública e privada do Rio Grande Do Norte - Costa, Marcelo Menezes da (2013)
Currently, several models of management services from the public administration are in operation in Brazil following a global trend. Besides the traditional public management operated in SUS, there are ongoing experiments of privately management in the public health services. Accordingly, we have developed an investigation into two Psychosocial Care Centers operating between these two forms of financial resources management: the first is the CAPS II - PAR situated in the municipality of Parnamirim whose form is private and the second is the CAPS II West Christmas is that the municipal government. We seek to know the workings of services, planning forms and criteria for use of financial resources, identify differences between departments on ways to run and see how technicians and users participate in the planning and management of these resources. Documentary Research was conducted by the municipal Christmas and the financial administration of the CAPS service in Parnamirim. Were conducted an interview with manager (mental health coordinator of Natal) and another interview with an employee of planning department in the Health Department of Natal, an interview with the coordinator and financial administrator of CAPS - PAR and two groups of discussion taped conversation with semi structured script interviews with six technicians in CAPS PAR and six professionals crowded in CAPS - West.Differences were observed in the management of resources funded from four blocks of discussion and analysis of results, where the privately-run service for the direct management and bureaucracy without being discussed and planned spending on staff, as well as through meetings with users, the use of the financial resources available in box; already in service with municipal public administration there is a hierarchy, this answering the coordination of mental health and the local health department that centralizes resources and defines their spending. There are meetings with patients and families, but the demands are limited as to what can be sued because of the manager s authorization. Such differentiation would be related to differences in the articulation of public management with the different types of possible management in public services, where from the implementation of new public administration in the Brazilian s State Management Reform initiated in the second half of the 1990s, benefit management services with private regime, with autonomy and direct transfer of resources